CARICOM human resource development 2030 strategy : unlocking Caribbean human potential (CCS GeorgetownGY, 2018)
Outlines specific targeted outcomes in basic education (early childhood to secondary), tertiary and skills for lifelong learning sectors.
Keywords: HUMAN RESOURCES DEVELOPMENT